STRENGTHENING MEANINGFUL PARTICIPATION THROUGH PUBLIC INFORMATION DISCLOSURE IN ELECTION FINANCING: THE ROLE OF THE YOUNGER GENERATION IN SAFEGUARDING DEMOCRATIC PROCESSES IN INDONESIA - Rasyetyari; Ani Purwanti (Awang Long Law Review, 2026)
Elections and electoral processes constitute arenas of political contestation involving various stakeholders, including political parties, election participants, election management bodies, and public participation, as constitutionally guaranteed under the Constitution of the Republic of Indonesia of 1945 (UUD NRI 1945). However, this does not imply that the administration of elections and electoral processes is free from problems, as evidenced by the prevalence of corruption practices, vote manipulation, bribery, and the lack of transparency in campaign financing, which reflect the long-standing and intertwined challenges in electoral implementation. This scientific paper aims to identify, analyze, and understand the problems related to campaign finance transparency, as well as to seek ideal solutions by integrating technology through the utilization of machine learning as a decision support system. The research method employed is doctrinal legal research, with the research outcome formulated in the form of an ideal legal construction through legal reconceptualization. The recommendations proposed by the author include the necessity of conducting careful legal scrutiny through a comprehensive, sharp, and in-depth analysis of the scope, regulatory direction, and substantive content of the proposed regulations, as well as the need for synergistic and complementary coordination to support the supervision of campaign financing in Indonesia.